Precision diabetes: Lessons learned from maturity‐onset diabetes of the young (MODY). Issue 9 (16th June 2022) - Tosur, Mustafa; Philipson, Louis H
Abstract: Maturity‐onset of diabetes of the young (MODY) are monogenic forms of diabetes characterized by early onset diabetes with autosomal dominant inheritance. Since its first description about six decades ago, there have been significant advancements in our understanding of MODY from clinical presentations to molecular diagnostics and therapeutic responses. The prevalence of MODY is estimated as at least 1.1–6.5% of the pediatric diabetes population with a high degree of geographic variability that might arise from several factors in the criteria used to ascertain cases. GCK ‐MODY, HNF1A ‐MODY, and HNF4A ‐MODY account for >90% of MODY cases. While some MODY forms do not require treatment (i.e., GCK‐ MODY), some others are highly responsive to oral agents (i.e., HNF1A ‐MODY). The risk of micro‐ and macro‐vascular complications of diabetes also differ significantly between MODY forms. Despite its high clinical impact, 50–90% of MODY cases are estimated to be misdiagnosed as type 1 or type 2 diabetes. Although there are many clinical features suggestive of MODY diagnosis, there is no single clinical criterion. An online MODY Risk Calculator can be a useful tool for clinicians in the decision‐making process for MODY genetic testing in some situations. Molecular genetic tests with a commercial gene panel should be performed in cases with a suspicion of MODY. Unresolved atypical cases can be further studied by exome or genome sequencing in a clinical or research setting, as available. Abstract : In this mini‐review, we summarize the history of maturity‐onset of diabetes of the young (MODY), commonly encountered MODY forms, the clinical characteristics that should lead to MODY suspicion, and practical tips from diagnosis to management. In the era of exponential growth in genetics with its role in precision medicine in various disease states, our mini‐review highlights its utility in the field of diabetes and provides another convincing argument for expanding the accessibility of comprehensive genetic testing for all who deserve it.